Analisis Pengembangan Media Booklet dalam Pembelajaran Maharah Kitabah - Arniati; Mukhlisah; Suryati (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2025)
This study describes the development of Booklets as Arabic learning media in maharah kitabah to improve students' ability to write Arabic, especially in mufradat. The purpose of this writing is to be a solution to the problem of learning Arabic, especially in maharah kitabah, namely the weak ability of students to write each mufradat, be it in the letter itself or even the mufradat sentence directly. This research uses the development research method, which is a process in developing and validating products, with the ADDIE model which goes through several stages, namely analysis, design, development, implementation, and evaluation. This research focuses on media development for maharah kitabah. Maharah kitabah is one of the maharah that is considered the most difficult, because it expresses thoughts through writing, so students need these writing exercises. The results of this booklet media development show that students feel happy when learning kitabah using this booklet media.